Sustainable Degradation of Lignocellulosic Biomass - Techniques, Applications and Commercialization 2013
DOI: 10.5772/55088
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Lignocellulosic Biomass Using Microorganisms: Approaches, Advantages, and Limitations

Abstract: Additional information is available at the end of the chapter http://dx.doi.org/10.5772/55088 . IntroductionMuch of Earth s recent geologic history is dominated by periods of extensive glaciation, with relatively low global mean temperatures and correspondingly low atmospheric CO concentrations [ ]. The current interglacial period stands out as an anomaly because the atmospheric CO concentration has risen sharply above the range of approximately -parts per million by volume that has defined the past , years to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 144 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Most of these fungi are Ascomycetes, Deuteromycetes, or Basidiomycetes; they live on wood and degrade the wood components, thereby causing wood rots [71,72]. Brown rot fungi, for instance, constitute around 6-10% of wood decay fungi, and they not only degrade cellulose and hemicellulose but also modify lignin through a demethylation reaction [72][73][74]. It was reported that lignocellulose degradation occurs in the S2 layer of the cell wall via oxidation and hydrolysis mechanisms [75].…”
Section: Pretreatment Methods Of Lignocellulosementioning
confidence: 99%
See 1 more Smart Citation
“…Most of these fungi are Ascomycetes, Deuteromycetes, or Basidiomycetes; they live on wood and degrade the wood components, thereby causing wood rots [71,72]. Brown rot fungi, for instance, constitute around 6-10% of wood decay fungi, and they not only degrade cellulose and hemicellulose but also modify lignin through a demethylation reaction [72][73][74]. It was reported that lignocellulose degradation occurs in the S2 layer of the cell wall via oxidation and hydrolysis mechanisms [75].…”
Section: Pretreatment Methods Of Lignocellulosementioning
confidence: 99%
“…It was reported that lignocellulose degradation occurs in the S2 layer of the cell wall via oxidation and hydrolysis mechanisms [75]. White rots are the most effective fungi in degrading the main components of the cell wall (e.g., lignin, hemicellulose, and cellulose) [72][73][74].…”
Section: Pretreatment Methods Of Lignocellulosementioning
confidence: 99%
“…[22]. The pretreatment step is regarded as a crucial and costly unit process in converting lignocellulosic materials into fuels, and it is the major contributor to the costs of producing energy from biomass [23,24]. In contrast to physicochemical methods, biological pretreatment of lignocellulosic biomass is a safe, environmentally friendly, less energy intensive and cheap alternative [2,25].…”
Section: Biological Pretreatmentsmentioning
confidence: 99%
“…Biological pretreatment, in contrast to the thermochemical and physicochemical pretreatment methods, is an energy-saving and environmentally benign process, which breaks down the lignocellulosic matrix using microorganisms (fungi or bacteria) under liquid-state or solid-state fermentation (SSF) [20,21]. Fungi, including white-, brown-, and soft-rot fungi, possess highly efficient enzymatic systems that are responsible for the degradation of lignocellulosic materials.…”
Section: Introductionmentioning
confidence: 99%